The Danger of Illegal Drugs to Public Health from A Criminological and Regulatory Perspective - Zaky, Ahmad Fairuz; Maulana, Haris; Nurmaudi, Siti; Kartini, Ratu Mawar; Dikrurahman, Diky (International Journal of Social Service and Research, 2025)
The circulation of unlicensed drugs remains a significant public health concern in Indonesia, particularly among lower-income populations who often purchase medications from unregulated sources such as street vendors and informal shops. These drugs frequently lack verified safety standards, increasing the risk of harmful side effects. The inability to distinguish between genuine and counterfeit drugs, compounded by a lack of consumer knowledge and weak enforcement, contributes to the persistent distribution of unauthorized pharmaceutical products. This study aims to examine the legal regulations governing the distribution of drugs without a license and analyze the enforcement mechanisms applied to offenders. Employing normative juridical research methods, the study reviews and interprets existing legal frameworks including Law No. 17 of 2023 on Health, Regulation of the Minister of Health No. 10101/MENKES/PER/XI/2008 on Drug Registration, Presidential Regulation No. 80 of 2017 concerning the National Food and Drug Authority (BPOM), and BPOM Regulation No. 24 of 2021. The findings indicate that strict legal provisions prohibit the production, storage, promotion, or distribution of pharmaceutical products that do not meet safety, efficacy, and quality standards, with severe sanctions outlined in Article 435 of the Health Law. This study highlights the critical need for enhanced public awareness, stricter enforcement, and strengthened coordination among regulatory bodies to protect consumers from unsafe drug distribution and uphold public health standards.